2018
DOI: 10.1111/1755-0998.12942
|View full text |Cite
|
Sign up to set email alerts
|

New mitochondrial primers for metabarcoding of insects, designed and evaluated using in silico methods

Abstract: Insect metabarcoding has been mainly based on PCR amplification of short fragments within the "barcoding region" of the gene cytochrome oxidase I (COI). However, because of the variability of this gene, it has been difficult to design good universal PCR primers. Most primers used today are associated with gaps in the taxonomic coverage or amplification biases that make the results less reliable and impede the detection of species that are present in the sample. We identify new primers for insect metabarcoding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 57 publications
2
96
0
Order By: Relevance
“…In this study, we extend a previous in silico study of markers for insect metabarcoding (Marquina et al, 2018) by testing the optimal 16S and COI markers identified there in three different empirical settings. Targeting Malaise trap catches from three different sites at four different time points, we analysed homogenized insects and preservative ethanol from the same samples, and environmental DNA from soil samples taken at the same sites.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this study, we extend a previous in silico study of markers for insect metabarcoding (Marquina et al, 2018) by testing the optimal 16S and COI markers identified there in three different empirical settings. Targeting Malaise trap catches from three different sites at four different time points, we analysed homogenized insects and preservative ethanol from the same samples, and environmental DNA from soil samples taken at the same sites.…”
Section: Introductionmentioning
confidence: 93%
“…Two mitochondrial markers were selected for PCR amplification based on the findings of Marquina et al (2018). The COI marker was amplified using the primer pair BF2-BR1 ; see also Marquina et al, 2018), resulting in an amplicon of approximately 320 bp.…”
Section: Pcr and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…An ideal complementary marker should be easily amplified through the different subtaxa of the target group, while providing enough taxonomic resolution to discriminate between related species. The mitochondrial rRNA gene 16S has been offered as such a marker (Clarke et al, 2014;Deagle, Jarman, Coissac, Pompanon, & Taberlet, 2014;Marquina, Andersson, & Ronquist, 2018). To our knowledge, only a few studies have tested the potential of using 16S as a replacement for COI in insects in vitro (Clarke et al, 2014;Elbrecht et al, 2016;Epp et al, 2012), or as a complement (Alberdi, Aizpurua, Gilbert, & Bohmann, 2018), and only one study made use of both markers simultaneously in resolving ecological rather than methodological questions (Kaunisto, Roslin, SÀÀksjĂ€rvi, & Vesterinen, 2017).…”
Section: Introductionmentioning
confidence: 99%